Impact of the Carbonization Atmosphere on the Properties of Phosphoric Acid-Activated Carbons from Fruit Stones - A.M. Puziy; O.I. Poddubnaya; A. Martínez-Alonso; F. Suárez-García; A. Castro-Muñiz; J.M.D. Tascón (Adsorption Science & Technology)
Activated carbons were obtained by phosphoric acid activation of a mixture of fruit stones (apricot and peach) in two different atmospheres (argon and air) at various temperatures in the 400–1000°C range. The evolution of several characteristic parameters of the resulting carbons (bulk density, yield, BET surface area, ultramicropore, supermicropore and mesopore volumes and cation-exchange capacity) with activation temperature was examined. The above parameters were re-calculated on a volume basis (practical effectiveness) and a volume-yield basis (economic efficiency). It was concluded that carbons obtained in an argon atmosphere exhibit some practical advantages over those obtained in air regarding cation adsorption, although those obtained in air may represent an interesting alternative regarding porous structure.